136k views
1 vote
PLEASE HELP ASAP!!!

let f(x) = 2x^2 + x - 3 and g(x) = x - 1

find (g/f)(x) and state its domain.

User BowPark
by
5.2k points

1 Answer

5 votes

ANSWER


( (g)/(f) )(x) = (1)/( 2x+3)

The domain is:


x \\e1 \: or \: x \\e - (3)/(2)

Step-by-step explanation

The given functions are:


f(x) = 2 {x}^(2) + x - 3

and


g(x) = x - 1


( (g)/(f) )(x) = (g(x))/(f(x))


( (g)/(f) )(x) = \frac{x - 1}{2 {x}^(2) + x - 3 }

Factor the quadratic trinomial in the denominator.


( (g)/(f) )(x) = \frac{x - 1}{2 {x}^(2) +3 x - 2x- 3 }


( (g)/(f) )(x) = (x - 1)/( x(2x+3) -1 (2x + 3 ))


( (g)/(f) )(x) = (x - 1)/( (2x+3) (x-1))

Cancel the common factors,


( (g)/(f) )(x) = (1)/( 2x+3) \: where \: x \\e1 \: or \: x \\e- (3)/(2)

User Nithin Michael
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.